2018
DOI: 10.1002/smll.201800426
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Some Amorphous Materials for Supercapacitors

Abstract: A breakthrough in technologies having "green" and sustainable energy storage conversion is urgent, and supercapacitors play a crucial role in this area of research. Owing to their unique porous structure, amorphous materials are considered one of the best active materials for high-performance supercapacitors due to their high specific capacity, excellent cycling stability, and fast charging rate. This Review summarizes the synthesis of amorphous materials (transition metal oxides, carbon-based materials, trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(93 citation statements)
references
References 157 publications
1
79
0
1
Order By: Relevance
“…LIBs/SIBs and supercapacitors (SCs) have their respective advantages and disadvantages. Batteries have high energy density but with low power density, and SCs have the reverse properties . Although numerous research focused on the SCs devices based on the aqueous electrolyte, their working voltage is limited to the potential of water decomposition .…”
Section: Nb2o5 Electrodesmentioning
confidence: 99%
“…LIBs/SIBs and supercapacitors (SCs) have their respective advantages and disadvantages. Batteries have high energy density but with low power density, and SCs have the reverse properties . Although numerous research focused on the SCs devices based on the aqueous electrolyte, their working voltage is limited to the potential of water decomposition .…”
Section: Nb2o5 Electrodesmentioning
confidence: 99%
“…It is also important to note that amorphous or low‐crystalline materials were reported to have better electrochemical performance than their crystalline materials . The reason may be based on the nature of amorphous materials as follows: (i) the metastable structure and long‐range disordered atomic arrangement of amorphous materials lead to abundant defects and oxygen vacancies to intensify the diffusion and reaction of electrolyte ions; (ii) the short‐range order of amorphous materials facilitates the transformation of surface groups into active sites during electrochemical reaction; (iii) the more accessible pathway offered by the amorphous state for charges intercalating and de‐intercalating to facilitate electron transfer affords enhanced electronic conductivity; (iv) the nice flexibility of amorphous materials owing to the isotropic strain and stress during charging and discharging yields outstanding electrochemical stability …”
Section: Introductionmentioning
confidence: 99%
“…Thus, the XRD studies have confirmed the complexation of GO as rGO localized in the ZAP matrix. The conformation envelope of ZAPG2 yielded a smaller crystallite size of 32.2 nm than ZAP (69.2 nm) (Debye–Scherrer relation), paving the way for the improved electrochemical performance of ZAPG2 compared to that of the pure ZAP …”
Section: Resultsmentioning
confidence: 99%